Assessment of Seasonal Variations of Air Quality and AQI Status: Evidence from Chittagong, Bangladesh - Mir Md. Mozammal Hoque; Md. Moshiuzzaman Khan; Md. Eusuf Sarker; Md. Nuralam Hossain; Md. Sirajul Islam; Md. Mehedi Hasan Khan; Manik Shil; Md. Nazirul Islam Sarker (Indonesian Journal of Environmental Management and Sustainability, 2022)
With the rate of fast urbanization, the devasting effects of air pollution are spreading across the globe. Due to its connection to people’s health, air quality should be given more importance than other environmental measures. Air pollution is considered a cause of many human diseases. Therefore, this study intends to investigate seasonal variation of air quality and “Air Quality Index (AQI)” in Chittagong city due to its volume, large population density, and importance as a commercial capital city of Bangladesh. Air pollution data on PM10, PM2.5, NO2 , NOx, SOx, CO, and O3 levels have been collected from TV station, Khulshi Continuous Air Monitoring Station (CAMS). Component-specific analyzers have been used to continuously measure trace gases where O3 is observed with a UV photometric analyzer. This study detect the highest peak (PM2.5= 93.5 µg/m3, PM10= 210 µg/m3) in January and the lowest concentrations (PM2.5= 14.6 µg/m3 and PM10= 26.9 µg/m3 ) during July and August. The highest average concentration has been recorded as the value of SO2= 12.8 ppb (monsoon season), NO2= 64.9 ppb (pre-monsoon), CO= 1.2 ppm (monsoon) and lowest SO2= 3.2 ppb (winter season), NO2= 24.4 ppb (monsoon), CO= 0.6 ppm (pre-monsoon) respectively. The AQI values (223.6), (109.5), (194.5), and (317.3) indicate that the air quality during the pre-monsoon, monsoon, post-monsoon, and winter season is very unhealthy, cautious, unhealthy, and extremely unhealthy, respectively.